(In)Sincere Demeanor and (In)Sincere Language in Crisis Communication. (October 2022) - Clementson, David E.; Page, Tyler G.
Perceptions of a crisis communicator's sincerity drive reactions to an organization's response amidst a scandal. However, a spokesperson can nonverbally appear sincere while deceptively evading questions and can appear insincere while actually speaking sincere truths. Applying truth-default theory to crisis communication, we assess people's reactions to a spokesperson varying in sincerity through demeanor and language. In an experiment ( N = 801), adults from across the United States were randomly assigned to view one of four versions of a news interview. The stimuli present the spokesperson replying to questions with sincere or insincere demeanor and sincere language (conveying relevance and clarity) or insincere language (evasion and obfuscation). Results indicate that sincerity in demeanor and language interact to affect (a) account acceptance, (b) negative word-of-mouth intention, and (c) attribution of responsibility. But sincerity in language largely overrides behavioral impressions. Discussion concerns considering evasion and obfuscation as demeanor cues, when violations of relevance and clarity in language undercut a spokesperson's believability.